2013
DOI: 10.1371/journal.pone.0080020
|View full text |Cite
|
Sign up to set email alerts
|

Scales of Spatial Heterogeneity of Plastic Marine Debris in the Northeast Pacific Ocean

Abstract: Plastic debris has been documented in many marine ecosystems, including remote coastlines, the water column, the deep sea, and subtropical gyres. The North Pacific Subtropical Gyre (NPSG), colloquially called the “Great Pacific Garbage Patch,” has been an area of particular scientific and public concern. However, quantitative assessments of the extent and variability of plastic in the NPSG have been limited. Here, we quantify the distribution, abundance, and size of plastic in a subset of the eastern Pacific (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
124
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(145 citation statements)
references
References 53 publications
(60 reference statements)
16
124
2
3
Order By: Relevance
“…They found plastic particles in sediments from U.K. beaches and archived among the plankton in samples dating back to the 1960s with a significant increase in abundance over time. More recent evidence indicated that microplastic concentrations in the North Pacific subtropical gyre have increased by two orders of magnitude in the past four decades (Goldstein et al 2013). However, no change in microplastic concentration was observed at the surface of the North Atlantic gyre for a period of 30 years (Law et al 2010).…”
Section: Microplasticsmentioning
confidence: 99%
“…They found plastic particles in sediments from U.K. beaches and archived among the plankton in samples dating back to the 1960s with a significant increase in abundance over time. More recent evidence indicated that microplastic concentrations in the North Pacific subtropical gyre have increased by two orders of magnitude in the past four decades (Goldstein et al 2013). However, no change in microplastic concentration was observed at the surface of the North Atlantic gyre for a period of 30 years (Law et al 2010).…”
Section: Microplasticsmentioning
confidence: 99%
“…All plastic sampled was collected using a manta net (1 × 0.17 m, 333 micron mesh), designed and manufactured by Oceans Instruments, San Diego (Brown and Cheng, 1981;Goldstein et al, 2013;Reisser et al, 2013). One station in each of the three areas of interest was sampled on four occasions during the study period ( Table 1).…”
Section: Data Collectionmentioning
confidence: 99%
“…So far, studies that have physically measured and analyzed concentrations in coastal waters were equally unable to detect significant changes or increasing trends over multi-decadal time frames (see Gilfillan et al, 2009;Goldstein et al, 2013). Two possible statistical considerations may explain why increases in plastic production and waste outputs to sea are not reflected in field measurements to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, concerns include those relating to inter-study comparisons due to inconsistencies in methods and units reported, and the confounding patterns of spatial and temporal variability (e.g. Doyle et al, 2011;Goldstein et al, 2013). Variables, that influence sampling, need to be understood to aid in method standardisation or the development of best practice guidelines.…”
Section: Sampling Considerationsmentioning
confidence: 99%